2023
DOI: 10.1523/jneurosci.0626-23.2023
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Circuits Amplify Corticofugal Signals and Drive Feedforward Inhibition in the Inferior Colliculus

Abstract: The inferior colliculus (IC) is a midbrain hub critical for perceiving complex sounds such as speech. In addition to processing ascending inputs from most auditory brainstem nuclei, the IC receives descending inputs from auditory cortex that control IC neuron feature selectivity, plasticity, and certain forms of perceptual learning. Although corticofugal synapses primarily release the excitatory transmitter glutamate, many physiology studies show that auditory cortical activity has a net inhibitory effect on I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…To test the above hypothesis, we first performed anti-GAD and anti-PV immunostaining using brain slices containing the IC from SOM-IRES-Cre×Ai14 and VGAT×Ai14 mice, respectively. GAD and VGAT, which are commonly used markers for GABAergic neurons (Ono et al, 2005;Ito et al, 2009;Oberle et al, 2023), are coexpressed in IC neurons (supplement figure 4A). We found that, in all IC subdivisions, no SOM+ neurons were labeled by anti-GAD immunostaining (Figure 4A; n=12 slices from N=3 mice), indicating that all SOM+ neurons in the IC are excitatory.…”
Section: Ic Pv+ Neurons Are Anatomically More Heterogenous Than Ic So...mentioning
confidence: 99%
“…To test the above hypothesis, we first performed anti-GAD and anti-PV immunostaining using brain slices containing the IC from SOM-IRES-Cre×Ai14 and VGAT×Ai14 mice, respectively. GAD and VGAT, which are commonly used markers for GABAergic neurons (Ono et al, 2005;Ito et al, 2009;Oberle et al, 2023), are coexpressed in IC neurons (supplement figure 4A). We found that, in all IC subdivisions, no SOM+ neurons were labeled by anti-GAD immunostaining (Figure 4A; n=12 slices from N=3 mice), indicating that all SOM+ neurons in the IC are excitatory.…”
Section: Ic Pv+ Neurons Are Anatomically More Heterogenous Than Ic So...mentioning
confidence: 99%